2014
DOI: 10.1002/jcc.23563
|View full text |Cite
|
Sign up to set email alerts
|

Fast, metadynamics‐based method for prediction of the stereochemistry‐dependent relative free energies of ligand–receptor interactions

Abstract: The computational approach applicable for the molecular dynamics (MD)-based techniques is proposed to predict the ligand-protein binding affinities dependent on the ligand stereochemistry. All possible stereoconfigurations are expressed in terms of one set of force-field parameters [stereoconfiguration-independent potential (SIP)], which allows for calculating all relative free energies by only single simulation. SIP can be used for studying diverse, stereoconfiguration-dependent phenomena by means of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 63 publications
1
11
1
Order By: Relevance
“…Differences between the global minimum (corresponding to the ligand located in the binding cavity) and the “plateau” region (corresponding to the ligand in the bulk solution, outside the receptor) for considered FEPs both were larger than those expected on the basis of experimental data (Jozwiak et al 2010 ; Toll et al 2012 ). Recent results (Plazinska et al 2014 ) obtained for the fenoterol–β 2 -AR system which were in a good agreement with available thermodynamic data confirm that inaccuracies inherent in the force field and the initial location of the ligand were rather small. We therefore speculated that repulsive interactions between the N-terminus region and the ligand molecule (both bear a positive charge) cause the increase of the free energy.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Differences between the global minimum (corresponding to the ligand located in the binding cavity) and the “plateau” region (corresponding to the ligand in the bulk solution, outside the receptor) for considered FEPs both were larger than those expected on the basis of experimental data (Jozwiak et al 2010 ; Toll et al 2012 ). Recent results (Plazinska et al 2014 ) obtained for the fenoterol–β 2 -AR system which were in a good agreement with available thermodynamic data confirm that inaccuracies inherent in the force field and the initial location of the ligand were rather small. We therefore speculated that repulsive interactions between the N-terminus region and the ligand molecule (both bear a positive charge) cause the increase of the free energy.…”
Section: Resultssupporting
confidence: 77%
“…[ 3 H]-CGP-12177 and [ 3 H]( R , R )-methoxyfenoterol) revealed significant differences between the thermodynamic characteristics of binding of the fenoterol stereoisomers to different conformations of β 2 -AR (Toll et al 2012 ). Subsequent molecular simulations confirmed experimentally determined thermodynamic data for binding (∆G 0 , ∆H 0 , ∆S 0 ) and showed that structurally similar compounds (stereoisomers of fenoterol), the full agonists of β 2 -AR, bind to the inactive and active conformational states of β 2 -AR with different affinities and thermodynamic data (Jozwiak et al 2010 ; Toll et al 2012 ; Plazinska et al 2014 ).
Fig.
…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…The acceptance ratio is only related to the parameters in the temperature space, and it dependent on the extensive quantities implicitly, that is the potential energy E . Therefore, when the system size increases, the exchange rate will not decrease in PCST, this is different from parallel tempering, which usually employs more than 20 copies . In practice, only 2–3 copies are enough to maintain a high rate of exchange between neighboring copies.…”
Section: Methodsmentioning
confidence: 99%
“…. An important feature of this protocol is that the acceptance ratio is only related to the parameters in the temperature space, whereas it does not have an explicit dependence on the extensive quantities, i.e., the potential energy E. Therefore, compared with parallel tempering, which usually employs more than 20 copies, [39][40][41][42][43][44] this method does not suffer from a decrease of exchange rate with the increase of the system size. In practice, only 2-3 copies are employed, yet it is still capable of maintaining a high rate of exchange between neighboring copies.…”
Section: A Temperature-based Enhanced Samplingmentioning
confidence: 99%